Monte Carlo dosimetry of a new 90Y brachytherapy source - Junxiang, Wu; Shihu, You; Jing, Huang; Fengxiang, Long; Chengkai, Wang; Zhangwen, Wu; Qing, Hou; Chengjun, Gou (Journal of Contemporary Brachytherapy, 2015)
Purpose: In this study, we attempted to obtain full dosimetric data for a new 90 Y brachytherapy source developed by the College of Chemistry (Sichuan University) for use in high-dose-rate after-loading systems. Material and methods : The dosimetric data for this new source were used as required by the dose calculation formalisms proposed by the AAPM Task Group 60 and Task Group 149. The active core length of the new 90 Y source was increased to 4.7 mm compared to the value of 2.5 mm for the old 90 Sr/ 90 Y source. The Monte Carlo simulation toolkit Geant4 was used to calculate these parameters. The source was located in a 30-cm-radius theoretical sphere water phantom. Results : The dosimetric data included the reference absorbed dose rate, the radial dose function in the range of 1.0 to 8.0 mm in the longitudinal axis, and the anisotropy function with a  in the range of 0° to 90° at 5° intervals and an r in the range of 1.0 to 8.0 mm in 0.2-mm intervals. The reference absorbed dose rate for the new 90 Y source was determined to be equal to 1.6608 ± 0.0008 cGy s –1 mCi –1 , compared to the values of 0.9063 ± 0.0005 cGy s–1 mCi–1 that were calculated for the old 90 Sr/ 90 Y source. A polynomial function was also obtained for the radial dose function by curve fitting. Conclusions : Dosimetric data are provided for the new 90 Y brachytherapy source. These data are meant to be used commercially in after-loading system.